The Impact of Firms' Carbon Emissions on Financial Performance and the Role of Innovation: Evidence from Türkiye - Musa Özçelik; Seren Aydıngülü Sakalsız (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Carbon emissions, one of the main causes of climate change and environmental degradation, have recently become extremely important. In parallel, firms' disclosure of their environmental performance and activities to reduce carbon emissions are viewed positively by stakeholders and society. The question arises whether firms' activities to reduce carbon emissions create additional costs for firms or reduce their costs. In this study, we investigate the relationship between carbon emissions and firms' financial performance. We also examine the moderating effect of innovation on the relationship between carbon emissions and financial performance. The lack of a study on developing countries reveals the importance of this study. Within the scope of the analysis, 14 firms in the BIST Sustainability Index with carbon emissions and innovation data between 2017-2021 were included. Using the random effects model, we find that carbon emissions have a negative effect on firms' return on assets and return on equity, and this negative effect turns positive with innovation. On the other hand, no statistically significant effect was found between Tobin's q value and carbon emissions and innovation. The study shows that firms should adopt proactive environmental strategies and organize their resources and investments to manage their financial performance well.